PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR DEVIANT BEHAVIOR PREVENTION IN PROFESSIONAL EDUCATION ORGANIZATIONS - Sergeeva, Marina; Litvishkov, Vladimir; Nikitin, Alexander; Salun, Sergey; Kalinina, Julia; Nagornova, Ekaterina; Lobanova, Olga (Revista Inclusiones, 2019)
Current changes in Russian society highlight the issues of helping adolescents who express deviant behavior, as well as the development of complex preventive measures, rehabilitation, and socialization of this group of youth. Despite the increasing role of upbringing in the education system, not enough attention is paid to preventive activities in modern educational practice. In a number of cases, preventive activities are mostly formal in nature and administrative measures of influence on students prevail, which significantly complicates the upbringing of a socially adapted personality of a future professional. One of the main state tasks is the formation of a stable and healthy society. Youth is, therefore, an object of national and government interests, since the fate of society and nation depends on the habitual behavior, lifestyle, and personal qualities of the modern youth. Preventive action is a crucial and vital aspect of social control. Social control over deviant behavior and, most importantly, over crime as its most acute form includes battling it with punishment (repression) and prevention. At present, the crisis of punishment, criminal policy and criminal justice, and state and police control are generally recognized ideas in most countries. Deviant manifestations are not unique and new, but their study is becoming especially relevant at a turning point in the development of Russian society today. In contemporary society, the interaction between the individual, family, and society takes place in the context of a qualitative transformation of social relations, which causes both positive and negative changes in various areas of social life.